Triptolide and management of systemic malignancies besides pancreatic carcinomas - Kapoor, Shailendra (The WJG Press and Baishideng, 2009)
The recent article by Zhou et al was highly interesting and thought provoking. The authors have clearly shown that triptolide administration is associated with up-regulation of the Bax gene, resulting in an attenuating effect on cell growth in gastrointestinal malignancies such as pancreatic carcinomas. The article by Zhou et al is all the more important because it highlights the rapidly increasing role of triplodide in the management of systemic malignancies. For instance, triptolide acts on the PI3K/Akt/NF-κB pathway, thereby enhancing apoptosis secondary to the administration of bortezomib in multiple myeloma cells. Similar synergisms are seen when triptolide is administered along with 5-fluoruracil for the management of colonic carcinomas. Similarly, triptolide causes down-regulation of the Bcl-2 gene, resulting in control of cell growth in tumors, such as glioblastoma multiformes.